Synthesis, Characterization and Evaluation the Biological Activities of some new Transition Metal Complexes with Organic Ligand formamidine - Alataby, Ghadeer; Aldabbagh, Areej Kamal Assim (Iraqi Journal of Science, 2026)
Novel formamidine transition metal complexes were synthesized and thoroughly investigated through a reaction between various metal ions (Mn(II), Fe(II), Pd(II), Rh(III), Pt(IV), and Mo(VI)) and N,N-bis-(m-nitroaniline), resulting in air-stable complexes with geometrically distinct structures, including octahedral arrangements for Fe(II), Rh(III), Pt(III), and Mo(VI), a square planar configuration for Pd(II), and a tetrahedral structure for Mn(II). The structures of these compounds were identified using various techniques. IR spectra verified how the formamidine group act as bidentate N2 ligand chelating with the metal ions. Mass spectroscopy confirmed the suggested geometries. Studies have done by pyrolysis (TGA and DSC curve) shown that water excesses could be coordinated with metal complexes. 1H-NMR and magnetic sensitivity have also confirmed the existence of the ligand (HL) and consequently complexation with the metals. Besides, elemental micro-analysis, ultraviolet-visible spectroscopy, conductivity and melting points examination were implemented. The antioxidant activity of the compounds was finally assessed using the DPPH as free radical method. Gallic acid was used as a standard substance, has determined an IC50 value for the achieved complexes, which are potentially able to DPPH scavenge free radicals. Biological activity of the prepared ligand and its synthesized complexes has assessed against bacterial species, one of Gram-positive bacteria and the other was Gram negative bacteria, as well as fungi screening. The ligand [LNO2] did not appear to exert any effort towards the Stab positive bacteria and the Esch negative bacteria at the concentration used, while the participation of the complexes was higher compared to the ligand next to the positive and negative bacteria in concentration. The hostility of iron, rhodium and molybdenum was not observed at the concentration of the complexes and even the participation of platinum in the bacteria. Only the gram negative was not given to the body, knowing that the metal salts were more effective than the ligand. Inhibition of the ligand [HLNO2] against the fungus.